The Relation of Deworming with Nutritional Status of Elementary School Students in Sicanang - Yuni Sarni; Etti Sudaryati; Nurmaini Nurmaini (International Journal Labs, 2022)
Related to environmental sanitation and behavior which results in a decrease in health conditions, nutritional status, intelligence levels, and productivity of sufferers, causing economic losses. helminthiasis with BMI/U nutritional status, using a descriptive correlation design with a cross-sectional approach. Sample 103 students of SD Negeri 066669 (IV number 42 and V total 61) with purposive sampling technique, namely inclusion and exclusion criteria. Data analysis was univariate analysis with frequency distribution, and bivariate analysis used Spearman rank ( p <0.05). Most helminthiases were in the non-wormed category 87.4%. There was a significant relationship between helminthiasis and nutritional status BMI/U p value = 0.002. That there is a significant correlation between helminthiasis and the nutritional status of BMI/U due to personal hygiene and a slum environment, especially the lack of clean and healthy living behavior (PHBS).